2005
DOI: 10.4049/jimmunol.174.10.6184
|View full text |Cite
|
Sign up to set email alerts
|

Enforced Expression of Spi-B Reverses T Lineage Commitment and Blocks β-Selection

Abstract: The molecular changes that restrict multipotent murine thymocytes to the T cell lineage and render them responsive to Ag receptor signals remain poorly understood. In this study, we report our analysis of the role of the Ets transcription factor, Spi-B, in this process. Spi-B expression is acutely induced coincident with T cell lineage commitment at the CD4−CD8−CD44−CD25+ (DN3) stage of thymocyte development and is then down-regulated as thymocytes respond to pre-TCR signals and develop beyond the β-selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 71 publications
0
57
1
Order By: Relevance
“…It is possible, however, that low levels of endogenous OBF-1 protein exist in a subset of thymic populations, be it T or thymic B cells. It was recently shown that overexpression of Spi-B in DN3 thymocytes can reverse T lineage commitment and block ␤-selection due to impaired induction of Egr proteins (42), which, however, was not observed in our mice.…”
Section: Discussioncontrasting
confidence: 45%
“…It is possible, however, that low levels of endogenous OBF-1 protein exist in a subset of thymic populations, be it T or thymic B cells. It was recently shown that overexpression of Spi-B in DN3 thymocytes can reverse T lineage commitment and block ␤-selection due to impaired induction of Egr proteins (42), which, however, was not observed in our mice.…”
Section: Discussioncontrasting
confidence: 45%
“…This is similar to what is observed in Klf4Tg mice. Moreover, SpiB overexpression in DN2 thymocytes has been shown to lead to a blockage at the DN2-to-DN3 transition [40]. Thus, the defects in Klf4Tg mice may partly be caused by elevated levels of Id1 and SpiB or decreased levels of HEBalt.…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral transduction and FTOC were performed as described previously [40]. Briefly, sorted cells were infected, transduced with viral supernatant and seeded onto deoxyguanosine-depleted day 15 C57BL/6 host lobes in Terasaki microwell plate hanging drop cultures for 1 day, and the thymus lobes were then transferred to a freshly prepared filter/ sponge for regular thymus organ culture conditions.…”
Section: Retroviral Transduction and Fetal Thymic Organ Culturementioning
confidence: 99%
“…However, it is also required for the development and function of other cell types, including hematopoietic stem cells (Iwasaki et al, 2005), multipotent progenitors (Wontakal et al, 2011), myeloid cells (Ghani et al, 2011) and B cells (Houston et al, 2007). Forced overexpression of PU.1 can divert early T cells to a myeloid lineage (Anderson et al, 2002;Dionne et al, 2005;Lefebvre et al, 2005;Laiosa et al, 2006b). However, in the context of T-cell development the progenitors are normally protected from diversion, even while expressing high levels of PU.1, by their exposure to Notch signaling from the environment (Franco et al, 2006;Laiosa et al, 2006b) (Fig.…”
Section: Introductionmentioning
confidence: 99%